Are two naïve and distributed heads better than one? Factors influencing the performance of teams in a challenging real-time task - Blanchard, Matthew D.; Kleitman, Sabina; Aidman, Eugene (Frontiers in Psychology, 2023)
Collective decisions in challenging dynamic tasks, can be influenced by multiple factors including quality and quantity of communication, the operational conditions, and individual differences. Most studies of teams examine performance under a single operational condition (static task characteristics) but many real-world tasks are dynamic, thus the task characteristics may change. This study examined the “two heads are better than one” effect (2HBT1) on two performance metrics (accuracy and speed) in a challenging simulated driving task under different operational conditions (Kleitman, Jackson et al., 2022). We also investigated the influence of communication quality (optimality of timing and accuracy of instructions) and communication volume (duration and speaking turns) on team performance under different operational conditions. Participants completed a simulated driving task under two operational conditions (normal and fog) as individual drivers (N=134) or two-person teams (driver and navigator; N=160 with 80 teams). The fog condition was characterized by sudden reduced visibility for the driver but not the navigator. The normal condition was characterized by high visibility for both. Traditional and novel communication metrics were captured by measuring the quantity of communication and coding the quality of communication (helpful: well-timed and accurate; or harmful: poorly timed and/or inaccurate). Participants were also measured on demographics and a range of cognitive and personality constructs which were used as control variables in the analyses. Outcomes varied based on the operational condition for teams and individual drivers. Teams had higher accuracy (fewer collisions) than individuals during the normal condition, but teams had lower speed during the fog condition. Harmful communication was a positive predictor of collisions during the normal condition and helpful communication was a negative predictor of speed during the fog condition. Our novel measure of communication quality was a stronger predictor of collisions, but volume of communication was a stronger predictor of speed. Thus, the content of communication was more important for accuracy (collisions) and the volume of communication was more important for speed. Overall, results indicate when team performance thrives and succumbs compared with individual performance and informs theory about the 2HBT1 effect and team communication under different operational conditions.